Self-selection bias or decision inertia? Explaining the municipal bond "competitive sale dilemma". Issue 1 (5th March 2018) - Liu, Gao
Abstract : Purpose: Although most empirical studies find that competitive bidding can reduce the interest cost, the municipal bond primary market is dominated by negotiating offerings. The purpose of this paper is to investigate this dilemma by empirically testing two hypotheses: self-selection bias and decision inertia hypotheses. Design/methodology/approach: Logistic regressions and Heckman procedures are used to examine data from the California municipal bond primary market. Findings: The paper finds that while information asymmetry does affect the selection of underwriting approach, self-selection bias cannot explain the cost difference between the two sale approaches. On the other hand, decision inertia has the highest explanatory power in the selection of sale approaches. Originality/value: This paper provides a new explanation for the "competitive sale dilemma" from the perspective of decision inertia. The authors document that state and local governments show a greater propensity of adhering to previous choices, particularly in a context in which the outcome is uncertain or actors have little knowledge in comparing the outcome of the alternatives.